Peningkatan Literasi Keuangan melalui Pelatihan Financial Life Skill bagi Pelaku Usaha Mikro Kecil dan Menengah di Desa Sumberarum Kecamatan Tempuran - suci nasehati sunaningsih; Agustina Prativi Nugraheni; Nibras Anny Khabibah (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2022)
MSMEs are one of the drivers of the economy in Indonesia. MSMEs have a major contribution to the Gross Domestic Product in Indonesia. However, MSMEs have many limitations, including the limited ability of owners/managers to manage MSME business finances. This also happened to the owners of MSMEs in Sumberarum Village, Tempuran, Magelang. This limited ability creates problems such as ignorance of the owners/managers about the net profit they get, as well as poor cash management. Therefore, the owners/managers of MSMEs in Sumberarum Village need socialization and assistance regarding literacy and financial management. Community service in Sumberarum Village is carried out through literacy socialization and financial management for MSME owners/managers. Furthermore, the socialization was continued with financial management assistance through monitoring of financial records that had been carried out by the owners/managers of the MSMEs. After monitoring and evaluation, the results show that 70% of the sample has done good financial records. This program is expected to equip MSME owners/managers to have the right financial management skills so that they can increase MSME business profits.